Subepithelial Tumor-like Gastric Cancer - Kyoungwon Jung; Moo In Park (Yong Chan Lee, 2021)
Subepithelial tumor-like gastric cancer (SET-like GC) is a special type of gastric cancer with a relatively low prevalence of approximately 1%. Diagnosing SET-like GC is challenging because the tumor is often covered with normal mucosa. The mechanisms of occurrence of SET-like GC include: 1) excessive infiltration of lymphocytes in the cancer, 2) intensive secretion of mucin by mucinous adenocarcinoma, 3) excessive fibrosis around the cancer, and 4) adenocarcinoma arising from heterotopic gastric glands in the submucosa. It is important to be aware of the endoscopic features of SET-like GC to differentiate it from other subepithelial tumors, to recognize the possibility of SET-like GC, and to make a diagnosis before treatment. In this review, we summarized the epidemiologic and clinicopathologic characteristics of SET-like GC.